Evaluation of the indication of BRCA1/2 genetic tests in Iranian women and acceptance rate of risk‐reducing surgeries in BRCA mutation carriers. Issue 2 (12th January 2022) - Vasigh, Mahtab; Eslami, Bita; Elahi, Ahmad; Kaviani, Ahmad; Shirkoohi, Reza; Majidzadeh, Keivan; Nazarian, Newsha; Omranipour, Ramesh
Abstract: Background: A higher risk for breast and ovarian cancer has been reported in BRCA carriers and prophylactic surgeries are proposed to reduce this risk. This retrospective cohort study has evaluated the indication of BRCA1 / 2 genetic tests in Iranian women and the rate of women's acceptance of prophylactic surgeries recommended by the surgeon. Methods: Medical records of 147 high‐risk women according to NCCN clinical practice guidelines who referred for BRCA mutations testing were assessed. Individual information, indications for BRCA1 / 2 genetic testing and their results, physician recommendations, and type of accepted surgery were registered. To evaluate the current status of women an active visit follow‐up every six months was conducted. Results: The mean age of women was 43.40 ± 10.94 and the median follow‐up time was 1.92 years. Genetic test results showed 49(33.3%) women were positive for either BRCA1 / 2 mutations. Although the occurrence of breast cancer younger than 40 was the most common indication for genetic tests (26.5%), positive breast cancer history in first‐degree relatives and two relatives younger than 50 was the most common indications with positive results. The rate of acceptance of prophylactic mastectomy and bilateral salpingo‐oophorectomy was (14.3% and 34.7%) in BRCA mutation carriers. Conclusion: If the onset of breast cancer at a young age (less than 40) will be the only indication for a BRCA analysis, the rate of a positive result (12.8%) is very low. Further studies are warranted to evaluate the age limit for genetic testing in our country. Prophylactic mastectomy acceptance is very low in BRCA1 / 2 carriers in our centers. Abstract : In Iran, the occurrence of breast cancer younger than 40 is the most common indication for genetic tests. However, positive genetic test results in first‐degree relatives, and two relatives with a history of breast cancer younger than 50, are the most common indications with positive results. Furthermore, the rate of acceptance of prophylactic mastectomy and bilateral salpingo‐oophorectomy is still low in our country.